Research on the Application of Legal Theory Under the Smart Court System - Shu Wang; Siqi Lai; Kaiyan Xiao (Law and Economy, 2024)
Cutting-edge technologies such as networking, digitalization, and artificial intelligence have enabled judicial operations, which have had a profound impact on the traditional judicial order, including the judicial structure at the structural level, the governance rules at the entity level, and the technology embedding at the application level. This requires that legal values be constructed in a contemporary manner in combination with different scenarios, and that the public be more concretely and intuitively approach the values of judicial fairness and justice through diversified and visual digital expressions. Only by accurately grasping the construction and application orientation of artificial intelligence technology in the court system can we effectively enhance judicial capacity and achieve a higher level of court construction.